Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1371/journal.ppat.1011146
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of widespread benzimidazole drug resistance in Ancylostoma caninum from domestic dogs throughout the USA and discovery of a novel β-tubulin benzimidazole resistance mutation

Abstract: Ancylostoma caninum is an important zoonotic gastrointestinal nematode of dogs worldwide and a close relative of human hookworms. We recently reported that racing greyhound dogs in the USA are infected with A. caninum that are commonly resistant to multiple anthelmintics. Benzimidazole resistance in A. caninum in greyhounds was associated with a high frequency of the canonical F167Y(TTC>TAC) isotype-1 β-tubulin mutation. In this work, we show that benzimidazole resistance is remarkably widespread in A. cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 62 publications
1
29
1
Order By: Relevance
“…Our small‐scale study demonstrated absence of detectable alleles in A. caninum and U. stenocephala associated with benzimidazole resistance. Recently Venkatesan et al 11 demonstrated widespread β‐tubulin F167Y(TTC > TAC) mutation present in 50% (156/314) dogs infected with A. caninum using the ‘nemabiome’ approach 11 and Leutenegger et al 10 in 11% (54/511) using A. caninum allele‐specific qPCR tests. In AU6 A. caninum , the persistent shedding of A. caninum , despite repeated treatment reported by the owner, is therefore attributed to re‐infection or non‐compliance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our small‐scale study demonstrated absence of detectable alleles in A. caninum and U. stenocephala associated with benzimidazole resistance. Recently Venkatesan et al 11 demonstrated widespread β‐tubulin F167Y(TTC > TAC) mutation present in 50% (156/314) dogs infected with A. caninum using the ‘nemabiome’ approach 11 and Leutenegger et al 10 in 11% (54/511) using A. caninum allele‐specific qPCR tests. In AU6 A. caninum , the persistent shedding of A. caninum , despite repeated treatment reported by the owner, is therefore attributed to re‐infection or non‐compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Using a locally curated reference database with ITS‐2 sequences for A. caninum , A. ceylanicum , A. braziliense , Ancylostoma duodenale , Nectar americanus and U. stenocephala , we assigned species to ASVs with the aid of phylogenetic analysis in CLC Main Workbench. For isotype‐1 β‐tubulin, ASVs were assembled against a reference A. caninum isotype‐1 β‐tubulin sequence (DQ459314) in CLC Main Workbench and frequency of mutations Q134H(CAA > CAT), F167Y(TTC > TAC), E198A(GAA > GCA), E198L(GAA > TTA), E198V(GAA > GTA) and F200Y(TTC > TAC) identified according to Venkatesan et al 11 The data are available at LabArchives (https://doi.org/10.25833/91fj-cq08). Raw FastQ sequence data were deposited at SRA NCBI BioProject: PRJNA957571.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Validated resistance mechanisms in parasitic nematodes are restricted to mutations in the cytoskeletal targets of the benzimidazoles [5], but genetic tools in the model nematode Caenorhabditis elegans have helped to identify anthelmintic resistance mechanisms beyond drug target mutations [20]. These include mutations that affect the ability of drugs to accumulate within the worm by altering drug uptake, distribution, efflux, or metabolism [14,16,21,22].…”
Section: Introductionmentioning
confidence: 99%